Protective effect of Glycyrrhiza glabra roots extract on bone mineral density of ovariectomized rats - Galanis Dimitrios; Soultanis Konstantinos; Lelovas Pavlos; Zervas Alexandros; Papadopoulos Panagiotis; Galanos Antonis; Argyropoulou Katerina; Makropoulou Maria; Patsaki Anastasia; Passali Christina; Tsingotjidou Anastasia; Kourkoulis Stavros; et al. (BioMedicine, 2019)
Objective: The aim of this study was to evaluate the potential effect of the methanolic extract of plant Glycyrrhiza glabra roots on bone mineral density and femoral bone strength of ovariectomized rats. Methods: Thirty 10-month-old Wistar rats were randomly separated into three groups of ten, Control, Ovariectomy and Ovariectomy-plus-Glycyrrhiza in their drinking water. Total and proximal tibial bone mineral density was measured in all groups before ovariectomy (baseline) and after 3 and 6 months post ovariectomy. Three-point-bending of the femurs and uterine weight and histology were examined at the end of the study. Results: No significant difference was noted in bone density percentage change of total tibia from baseline to 3 months between Control and Ovariectomy-plus-Glycyrrhiza groups (+5.31% ± 4.75 and +3.30% ± 6.31 respectively, P = non significant), and of proximal tibia accordingly (+5.58% ± 6.92 and +2.61% ± 13.62, P = non significant) demonstrating a strong osteoprotective effect. There was notable difference in percentage change of total tibia from baseline to 6 months between groups Ovariectomy and Ovariectomy-plus-Glycyrrhiza (−13.03% ± 5.11 and −0.84% ± 7.63 respectively, P < 0.005), and of proximal tibia accordingly (−27.9% ± 3.69 and −0.81% ± 14.85 respectively, P < 0.001), confirming the protective effect of Glycyrrhiza glabra extract in preserving bone density of the Ovariectomy-plus-Glycyrrhiza group. Three-point-bending did not reveal any statistically significant difference between Ovariectomy and Ovariectomy-plus-Glycyrrhiza groups. Uterine weights of the Ovariectomy-plus-Glycyrrhiza group ranged between the other two groups with no statistically significant difference to each. Conclusions: Glycyrrhiza glabra root extract notably protected tibial bone mineral density loss in Ovariectomy-plus-Glycyrrhiza rats in comparison with ovariectomized rats, but did not improve biomechanical strength.